Pengaruh Harga, Promosi, Lokasi dan Kualitas Produk terhadap Keputusan Pembelian pada PT Campina Ice Cream Industry Tbk di Dringu Kabupaten Probolinggo - Choirun Nisa Santoso; R Abdul Haris; Dedi Joko Hermawan (Universitas Panca Marga, 2024)
This research was conducted on PT. Campina Ice Cream Industry Tbk in Dringu, Probolinggo Regency with the aim of knowing the effect of price, promotion, location, and product quality on purchasing decisions at PT. Campina Ice Cream Industry Tbk in Dringu, Probolinggo Regency. This type of research is a type of quantitative research. The population is consumers who make purchasing decisions at PT. Campina Ice Cream Industry Tbk and sampling using non-probability sampling, namely incidental side as many as 90 respondents. Data collection methods used in this study were interviews, documentation and questionnaires distributed to respondents. Data analysis methods in this study were validity test, reliability test, classic assumption test, multiple regression analysis, coefficient of determination and hypothesis testing using SPSS Version 23.0. The results of this study also show that price has a significant effect on purchasing decisions, promotion has a significant effect on purchasing decisions, location has a significant effect on purchasing decisions, and product quality has a significant effect on purchasing decisions.